Novel wavelet approach to current differential pilot relay protection. - Chi-Kong Wong (IEEE Transactions on power delivery)
This paper describes a novel technique for current differential pilot relay protection (CDPR) by using wavelet analysis. Power system CAD (PSCAD) is used to generate current signals at both ends of a transmission line in a typical system with fault at various locations. In this paper, discriminating between internal fault and external fault/change, identifying of faulted phase, and classifying fault type are achieved by using wavelet analysis. The simulation results show that this approach provides a high operating sensitivity for internal fault and remains stable for external fault/change.